2013
DOI: 10.1371/journal.pone.0079625
|View full text |Cite|
|
Sign up to set email alerts
|

Dopamine D1 Receptors Regulate the Light Dependent Development of Retinal Synaptic Responses

Abstract: Retinal synaptic connections and function are developmentally regulated. Retinal synaptic activity plays critical roles in the development of retinal synaptic circuitry. Dopamine receptors have been thought to play important roles in the activity-dependent synaptic plasticity in central nervous system. The primary goal of this study is to determine whether dopamine D1 receptor regulates the activity-dependent development of retinal light responsiveness. Accordingly, we recorded electroretinogram from wild type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 101 publications
(130 reference statements)
5
30
0
1
Order By: Relevance
“…These values compare closely to waveform amplitudes seen in mice at around P10 (mouse age equivalence to human newborns), with our recorded a-wave averages 19.86 ± 2.28 μV by P10. Additionally, these values compare closely to similar in-vivo studies in mice showing a-wave amplitudes around 50 μV in P13 mice, right at the time of eye opening (19). Taken together, these data suggest that light-mediated effects on the development of the mouse visual system could be a correlate of a light-mediated effect on the development of the human visual system.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…These values compare closely to waveform amplitudes seen in mice at around P10 (mouse age equivalence to human newborns), with our recorded a-wave averages 19.86 ± 2.28 μV by P10. Additionally, these values compare closely to similar in-vivo studies in mice showing a-wave amplitudes around 50 μV in P13 mice, right at the time of eye opening (19). Taken together, these data suggest that light-mediated effects on the development of the mouse visual system could be a correlate of a light-mediated effect on the development of the human visual system.…”
Section: Discussionsupporting
confidence: 86%
“…Physiological studies in the outer retina of young adult mice using electroretinograms (ERGs) and suction electrode techniques have been performed over the past few decades (10-18). Findings have confirmed that photoresponses mature over the few weeks following eye-opening (P12-P14), becoming relatively stable in terms of kinetics and sensitivity around P30 (adults) (14, 19). Relatively few experiments have been done in the developing mouse retina prior to eye opening.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…45 We also found that suppression of the b-wave and summed OP amplitudes by the D1R antagonist SCH39166 resembled the ERG phenotype of the D1R-KO mice. Similar results showing a reduction of the b-wave amplitude have been obtained by other authors working with D1R-KO mice 44,46,47 and D1R antagonist-treated goldfish. 41 However, in frogs, pharmacologic blockage of D1Rs increased the amplitudes of b-waves of both dark-and light-adapted ERGs.…”
Section: D1r-dependent Mechanism Of Apomorphine In Myopiasupporting
confidence: 90%
“…All these lines of evidence suggest that the retina may act as an intact connection to the anterior segment optic system as well as the visual cortex during early visual development (sketch map shown in Figure 7a). The 'bridge' role of the retina may be functionally consistent with that of dopamine receptors, which are thought to regulate synapse formation, synaptic transmission and light adaptation in the experience-dependent development of the retina [44,45].…”
Section: Discussionmentioning
confidence: 90%